Need for beta-blockade in hypertension reduced with long-term minoxidil. Issue 6134 (5th August 1978) - Brunner, H R; Jaeger, P; Ferguson, R K; Jequier, E; Turini, G; Gavras, H
Abstract : Sequential changes in plasma renin activity and urinary aldosterone and noradrenaline were assessed in eight patients with severe hypertension after minoxidil had been added to their treatment. Doses of 2.5–27.5 (mean 12.5) mg/day reduced the mean blood pressure from 166/113 +/-6/2 mm Hg to 124/88+/-4/2 mm Hg in one week. Plasma renin activity and urinary aldosterone and noradrenaline increased twofold to threefold initially but returned to baseline values within two to three weeks and remained unchanged during a mean follow-up of 5.1 months. Beta-blocking drugs were then withdrawn slowly in six patients without adverse effects, though blood pressure and heart rate increased in three patients, who required minimal doses of beta-blockers. Plasma renin activity and urinary aldosterone and noradrenaline did not change significantly after beta-blockade had been stopped. We conclude that the need for beta-blockade is greatly reduced with long-term minoxidil treatment and that it may be unnecessary in some patients.